STUDI MEKANISME KINETIKA REAKSI PERTUKARAN ION FE(III) ANTARA DUA JENIS LIGAN SIDEROPHORE BAKTERI (DESFERRIFERRIOXAMINE B DAN AZOVERDINE) DENGAN LIGAN EDTA - Handoko Darmokoesoemo; A.M. Albrecht Gary (The East Java Biological Society, 1995)
The kinetics of iron exchange and iron removal from two siderophore complex with use of ethylenediaminetetraacetic acid (EDTA) have been examined, using UV-Vis spectrophotometric method. Iron exchange between the ferric complexes of desferriferrioxamine B (siderophore produced by microorganism Azomonas macrocy-togenes) with EDTA was extremely slow under conditions at pH 7.4 and 25oC. Furthermore, pH dependence studies demonstrated that the exchange rate was accelerated as a function of increasing hydrogen ion concentration. Kinetics of iron removal from ferrioxamine B and the ferric complexe of azoverdine with excess of EDTA, show firt-order dependence on the concentration of the iron complex and hydrogen ion at 25oC with first-order rate constant of the dissociation of a ternary complex formed of (16 ±0.4) x 10-3s-1 and (1.3 ±0.2) x 10-2s-1 respectivy at pH region between 3.67 and 5.23. variation of pseudo first order rate constant kobs with hydrogen ion concentration shows a saturation kinetics at high constant ligand EDTA concentration (3.0 x 10-2 M) and at low pH region (3.67). the result were interpreted in terms of three-step mechanism, involving : (1) protonation of the ferrioxamine B comples and the ferric comples of azoverdine and (2) subsequent biomolecular reaction with EDTA.